Effect of a novel Lactobacillus paracasei starter on sourdough bread quality. (15th January 2019) - Mantzourani, Ioanna; Plessas, Stavros; Odatzidou, Maria; Alexopoulos, Athanasios; Galanis, Alex; Bezirtzoglou, Eugenia; Bekatorou, Argyro
Highlights: Novel, potentially probiotic, Lactobacillus paracasei K5 used as sourdough starter. The K5 breads had good quality (rising, acidity, organic acids, consumer preference). The K5 breads had more complex volatile profiles as shown by SPME-GC/MS. The appearance of rope spoilage was delayed (macroscopic and PCR-DGGE analysis). L. paracasei K5 can be used for good quality & extended shelf-life sourdough bread. Abstract: The novel Lactobacillus paracasei K5 strain, recently isolated from Greek cheese, was evaluated as potential sourdough bread starter. Breads were made using different amounts of L. paracasei sourdoughs as well as traditional sourdough for comparison. Quality characteristics of the breads (acidity and rising) were examined, as well as rope spoilage through macroscopic observations and molecular analysis (PCR-DGGE). The highest acidity levels (3.15 g lactic acid and 1.13 g acetic acid per kg of bread) and better resistance to rope spoilage were observed when bread contained 30% w/w L. paracasei K5 sourdough . Spoilage in the L. paracasei K5 breads was observed at 15–16 days, 5 days later than the control breads. In addition, L. paracasei K5 sourdough improved the bread sensory properties, as reflected by consumer preference and GC/MS analysis of aroma volatiles. Therefore, L. paracasei K5 can be successfully used for sourdough bread making with good quality and extended shelf-life.